(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the role of innovative pedagogical approaches in physics education and the methodological aspects of their practical implementation. The modern education system places special emphasis on fostering students’ active participation, independent thinking, and practical skills. In this process, interactive methods, the STEAM approach, digital technologies, and virtual laboratories play a crucial role. The article provides recommendations for organizing lessons based on innovative approaches, as well as criteria for evaluating their effectiveness. The research findings may contribute to the modernization of physics education.